A suitability modeling based on geographic information system for potential micro hydropower dam site - O. Setiawan; H.Y.S.H. Nugroho; N. Wahyuningrum; D. Auliyani; K.S. Hardjo (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Micro-hydropower plants are significant contributors of electricity and clean source of renewable energy. A nationwide or large watershed inventory of potential micro hydropower dam sites is lacking, hindering micro-hydropower development. Traditional ground survey approaches for locating micro-hydropower dam sites are expensive, time-consuming, laborious, and vulnerable to inconsistency. Geographic information system frameworks are commonly used, and they provide significant value to hydropower evaluation. A suitability approach for dam site identification is important in supporting the optimization of hydropower utilization in the context of watershed management and in eliminating the inconsistency of conventional approaches. The objective of this study was to identify potential sites for micro-hydropower dams on the basis of various parameters by using a suitability modeling approach based on geographic information system.METHODS: The Saddang Watershed was chosen as the study area, it is located in the South Sulawesi and West Sulawesi Provinces of Indonesia, and it is an example of a large watershed. The analytical hierarchy process was used for criterion weighting and to create a dam suitability index map based on the following criteria: geomorphometry, geology, rainfall, soil texture, and land use land cover. The developed dam suitability index map was validated by comparing it with existing dams by using the receiver operating characteristic curve. The identification of potential micro-hydropower dam sites involved overlay and query methods. It considers dam suitability index, proximity from road and settlement, existence of conservation forest, and the potential hydraulic head.FINDINGS: The dam suitability index map with five suitability classes was obtained, with the high and very high suitability indexes extending to 8.7 percent of the study area. These classes were typified by high drainage density, topographic wetness index, stream power index, low vegetation cover, moderate slope, situated on second or higher stream orders, normal temporal distribution of rainfall, and sandy clay loam soil texture with igneous and sedimentary complex rocks. The developed suitability model was sufficiently effective in determining dam suitability index, as indicated by a value greater than 0.9 of the area under the curve. A total of 635 potential dam locations were identified with high and very high suitability indexes, located on first or second stream orders, within a 4,000 m radius of roads and settlements, outside conservation forest areas, and with a potential hydraulic head greater than 20 meter.CONCLUSION: Integrating a dam suitability index map and restriction factors into a geographic information system framework, enabled a robust analysis for identifying potential sites of micro-hydropower dams. The proposed approach is expected to contribute to the advancement of renewable energy initiatives and water resource management within large watersheds. It is also expected to serve as a valuable resource for policymakers involved in the implementation of micro-hydropower projects and watershed management to support the achievement of renewable energy development targets.